2020
DOI: 10.1038/s41378-020-00201-6
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic platform for cultivating ovarian cancer spheroids and testing their responses to chemotherapies

Abstract: There is increasing interest in utilizing in vitro cultures as patient avatars to develop personalized treatment for cancer. Typical cultures utilize Matrigel-coated plates and media to promote the proliferation of cancer cells as spheroids or tumor explants. However, standard culture conditions operate in large volumes and require a high concentration of cancer cells to initiate this process. Other limitations include variability in the ability to successfully establish a stable line and inconsistency in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 39 publications
0
62
0
Order By: Relevance
“…Other than alginate[ 98 ], hydrogels such as chitosan, thermosensitive gelatin, agarose, Matrigel, collagen, P(NIPAM-AA), photoinitiative gelatin methacrylate (gelMA), PEGDA, and hyaluronic acid-MA have all been examined for facilitating spheroid formation and growth[ 94 ]. In addition to droplet-based microfludics, lab-on-a-chip technology also can integrate hanging drop networks[ 103 - 105 ], microwell[ 50 , 106 ], U-shape microstructure, or micropillar into the platforms for spheroid formation and on-chip culture. Microfluidic platforms outperform conventional static culture methods through the introduction of a perfusion flow that could improve oxygen and nutrient transportation, sustaining long-term cell culture[ 107 , 108 ].…”
Section: Spheroid Generation Methodsmentioning
confidence: 99%
“…Other than alginate[ 98 ], hydrogels such as chitosan, thermosensitive gelatin, agarose, Matrigel, collagen, P(NIPAM-AA), photoinitiative gelatin methacrylate (gelMA), PEGDA, and hyaluronic acid-MA have all been examined for facilitating spheroid formation and growth[ 94 ]. In addition to droplet-based microfludics, lab-on-a-chip technology also can integrate hanging drop networks[ 103 - 105 ], microwell[ 50 , 106 ], U-shape microstructure, or micropillar into the platforms for spheroid formation and on-chip culture. Microfluidic platforms outperform conventional static culture methods through the introduction of a perfusion flow that could improve oxygen and nutrient transportation, sustaining long-term cell culture[ 107 , 108 ].…”
Section: Spheroid Generation Methodsmentioning
confidence: 99%
“…Overall, 15 drug combinations were identified to have potent cytotoxic properties. Dadgar et al demonstrated the potential of a serial and parallel perfused multi-chamber microfluidic device to test various drug concentrations on spheroids generated by low cellular input ( Figure 4 B) [ 104 ].…”
Section: 3d Ovarian Cancer Modelsmentioning
confidence: 99%
“…Spheroids were stained for the epithelial marker EpCAM, proliferation marker Ki-67 and nuclear marker DAPI ( bottom ). Scale bar: 50 µm (Reproduced with permission from [ 104 ], Copyright © (2020), Springer Nature). Poly-HEMA, poly 2-hydroxyethylmethacrylate; PDMS, polydimethylsiloxane.…”
Section: Figurementioning
confidence: 99%
“…These advances have provided several beneficial properties, such as facile and efficient operation, homogeneous and large-scale tumor production, and throughput monitoring. In addition, microfluidic tumor platforms have been widely applied for exploration of the tumor microenvironment, [16,24,30,31] tumor progression, [21,32] chemotherapy, [18][19][20]27,28,33] imaging, [25,34] and tumor-specific molecule detection. [35] However, microfluidic progress enabling the real-time detection and synchronous evaluation of 3D tumor responses to drugs at various concentrations by using a single device, was limited.…”
Section: Introductionmentioning
confidence: 99%